ГЕОГРАФИЯ САБАҚЛАРЫН ИННОВАЦИЯЛЫҚ ТЕХНОЛОГИЯЛАРДАН ПАЙДАЛАНЫП ОҚЫТЫЎДЫҢ ӘҲМИЙЕТИ - Жиемуратова, Г.Ө. (FAN va JAMIYAT, 2021)
This article is about the theoretical and practical information about interactive and pedagogical technologies. The techniques for the formation of competence are given, such as knowledge, ability and skills by using interactive methods in geography lessons. The article analyzes the advantages of pedagogical technologies and the use of interactive methods in geography lessons.